Morphological variables as possible risk factors for the drivers of rubber tyred gantry cranes at the port of Felixstowe, UK - Watson, Estelle Dorothy (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSpor)--University of Stellenbosch, 2007.